Olfactory event-related potentials (OERPs) and trigeminal event-related potentials (TERPs) - a pilot study in Czech participants with normal sense of smell - Holy, Richard; Janouskova, Karla; Vasina, Libor; Maute, Eva; Kalfert, David; Maminak, Kristyna; Augste, Eva; Hlozek, Jiri; Schulz, Helene; Funda, David; Astl, Jaromir (Journal of applied biomedicine, 2023)
INTRODUCTION: In recent years, the evaluation of potential events related to olfactory events (OERPs) and trigeminal events (TERPs) has become increasingly important in the diagnosis of olfactory disorders. This technique is increasingly used in basic research and clinical practice to evaluate people suffering from olfactory disorders. PURPOSE OF THE STUDY: In a pilot project of the first investigations of OERPs and TERPs in the Czech Republic, we analyse the event-related potentials of the data of normosmic participants. METHODS: In the prospective study, 21 normosmic participants were enrolled for a 2-year period (5/2021-5/2023). OERPs/TERPs were recorded at the scalp vertex (electrode Pz/Cz). Odourants 2-phenylethanol/CO2 were used to selectively activate Nervus olfactorius/ Nervus trigeminus. Brain responses to olfactory/trigeminal stimuli (EEG) were recorded in 21/18 normosmic subjects. RESULTS: In the statistical analysis of the olfactory interval N1-P2 (age, gender), we found no statistically significant differences. In the statistical analysis of the trigeminal interval N1-P2 (age, gender) we found statistically significant differences in amplitude by gender (male amplitudes were higher than female amplitudes, p = 0.006). CONCLUSION: Our pilot data can function very well as an internal guide for ongoing and future olfactory research studies. Evaluation of the presence of OERPs appears to be an important parameter for the evaluation of olfactory disorders. The absence of OERPs is a strong indicator of the presence of olfactory dysfunction.
Keywords: Male; Trigeminal event-related potentials; Prospective Studies; Pilot Projects; Humans; poruchy čichu; pilotní projekty; prospektivní studie; Česká republika; mužské pohlaví; Czech Republic; Female; čich; Smell; evokované potenciály; Olfaction Disorders; ženské pohlaví; Odourants; Objective olfactometry; Olfactory event-related potentials; Evoked Potentials; lidé; Evaluation of smell